2022
DOI: 10.1080/21645515.2022.2144039
|View full text |Cite
|
Sign up to set email alerts
|

Safety of COVID-19 Pfizer-BioNtech (BNT162b2) mRNA vaccination in adolescents aged 12–17 years: A systematic review and meta-analysis

Abstract: The COVID-19 pandemic has severely affected adolescents. Safe and effective vaccines are pivotal tools in controlling this pandemic. We reviewed the safety profile of the BNT162b2 COVID-19 vaccine in adolescents using mostly real-world data to assist decision-making. We used random-effects model meta-analysis to derive pooled rates of single or grouped adverse events following immunization (AEFI) after each primary and booster dose, as well as after combining all doses. Reporting on over one million participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 50 publications
2
7
0
Order By: Relevance
“…However, our findings are consistent with other studies, including one in other provinces of South Korea, reporting the similar or milder clinical course of VAM in the East Asian population, 12 14 19 As such, our study can serve as a meaningful preliminary study for further nationwide or multicountry studies of East Asian countries. We found lower incidence of VAM in South Korea compared with that of other ethnicities (3.9–16.3 cases per 100,000), 19 34 35 36 37 38 and we also found that VAM cases were less severe. The incidence of VAM in South Korea is only 3.9 cases per 100,000 (135/3,481,287, as announced by the central disease control headquarters of Korea on May 20, 2022), while more than 80% of the adolescents aged 12 to 17 years were vaccinated with the second dose.…”
Section: Discussionsupporting
confidence: 60%
“…However, our findings are consistent with other studies, including one in other provinces of South Korea, reporting the similar or milder clinical course of VAM in the East Asian population, 12 14 19 As such, our study can serve as a meaningful preliminary study for further nationwide or multicountry studies of East Asian countries. We found lower incidence of VAM in South Korea compared with that of other ethnicities (3.9–16.3 cases per 100,000), 19 34 35 36 37 38 and we also found that VAM cases were less severe. The incidence of VAM in South Korea is only 3.9 cases per 100,000 (135/3,481,287, as announced by the central disease control headquarters of Korea on May 20, 2022), while more than 80% of the adolescents aged 12 to 17 years were vaccinated with the second dose.…”
Section: Discussionsupporting
confidence: 60%
“…Additional file 11 [ 47 , 87 ] summarizes single-arm evidence about long-COVID. Additional file 12 [ 54 , 67 , 77 , 139 , 153 ] summarizes single-arm evidence about events caused by the COVID-19 vaccine. Additional file 13 [ 49 , 50 , 58 , 82 , 99 , 113 , 142 ] summarizes single-arm evidence about health impacts during the pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…Following the previous experience of the global pandemic, such campaigns are only likely to be successful if they include adolescents as well as the elderly and adults, so our demonstration of the safety and immunogenicity of SCB-2019 vaccine in adolescents is important to inform planning of such campaigns. Other COVID-19 vaccines have been shown to be well tolerated and immunogenic in the age groups similar to ours [14][15][16][17], although there have been reports of rare cases of myocarditis and pericarditis in male adolescents following mRNA COVID-19 vaccines [18] and autoimmune diseases in children and adolescents [19].…”
Section: Discussionmentioning
confidence: 99%